Investigation of natural convection in triangular enclosure filled with porous media saturated with water near 4 °C - Öztop, Hakan Fehmi; Varol, Yasin; Pop, Ioan (Pergamon-Elsevier Science Ltd, 2009)
Analysis of natural convection in right-angle triangular enclosure filled with saturated cold water which has a density maximum around of 3.98 degrees C is performed numerically. The bottom and vertical wall of triangular enclosure is isothermal while inclined wall is adiabatic. But temperature of bottom wall is higher than that of vertical wall. Non-Boussinesq and Darcy models are used in mathematical formulations of governing equations. The calculations were performed for different Ra number as (50 <= Ra <= 1000) and ratio of height to base of enclosure (0.25 <= AR <= 1.0). It is observed that heat transfer decreases with the effects of density inversion and it decreases with increasing of aspect ratio. It is an interesting result that effects of aspect ratio becomes insignificant for Ra >= 1000. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Maximum density; Natural convection; Triangular enclosure; Porous media